Use of prototype automated blood culture system and gas-liquid chromatography for the analysis of continuous ambulatory peritoneal dialysis associated infection. Issue 3 (March 1997) - Catchpole, C R; Macrae, F; Brown, J D; Palmer, M; Healing, D E; Richards, N T; Elliott, T S
Abstract : AIMS: (1) To compare the recovery of organisms from continuous ambulatory peritoneal dialysis (CAPD) effluent fluid obtained from patients with clinical evidence of peritonitis, with an automated system (AS) and the Septichek blood culture system; (2) to evaluate the times to detection of organisms with the two systems; (3) to identify anaerobes from CAPD samples by extended anaerobic culture and gas-liquid chromatography (GLC). METHODS: 168 CAPD effluent fluid samples were studied, representing 157 episodes of peritonitis in 97 patients. CAPD samples were inoculated into two AS bottles-one anaerobic, one aerobic-and a Septichek bottle; samples were also examined for cell count, Gram stain, and direct culture. Culture bottles were then subcultured onto various media, and any organisms isolated were identified. After routine culture, GLC was performed on culture fluid in the anaerobic AS and Septichek bottles. When volatile fatty acids were detected, the broths were cultured anaerobically on specialised medium for a further five days. RESULTS: 147 organisms were isolated from the 168 samples: 96 (57%) yielded growth of significant organisms by direct culture, as compared to 129 (76.8%) by both AS and Septichek. There was no significant difference in isolation rates between AS and Septichek, but time to detection was more rapid with the AS system (p < 0.002). GLC showed volatile fatty acid in 15 specimens; of these, 14 subsequently grew anaerobic organisms. CONCLUSIONS: AS was comparable to Septichek for numbers of isolations. Speed to detection was faster with the AS, which may be an advantage in management of patients with CAPD peritonitis. GLC showed anaerobes in several cases which would not have been detected without prolonged anaerobic culture; thus anaerobic cultures are recommended for patients who are unresponsive to antimicrobials or who have evidence of bowel perforation.